2014
DOI: 10.1016/j.jpainsymman.2013.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Half-Body Irradiation With Tomotherapy for Pain Palliation in Metastatic Breast Cancer

Abstract: Lower HBI delivered with helical tomotherapy resulted in a well-tolerated regimen, without significant delay in chemotherapy schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…Our retrospective study shows that VMAT-based HBI is effective in palliation of pain, with relief in all measured scales of pain. Our findings are similar to results by another authors (8)(9)(10)12,13,16) are consistent with two prospective trials, where pain relief was reported in 76 and 73% of patients undergoing HBI (9,12). However, in both trials, radiotherapy was applied in less conformal techniques.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our retrospective study shows that VMAT-based HBI is effective in palliation of pain, with relief in all measured scales of pain. Our findings are similar to results by another authors (8)(9)(10)12,13,16) are consistent with two prospective trials, where pain relief was reported in 76 and 73% of patients undergoing HBI (9,12). However, in both trials, radiotherapy was applied in less conformal techniques.…”
Section: Discussionsupporting
confidence: 93%
“…The risk of radiation-induced pneumonitis, which tends to increase when a dose absorbed to a lung is higher than 6 Gy, is now lower (14). What is more, with the application of conformal techniques, doses to all OARs are reduced in comparison to those prescribed to PTV (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 2, the patients' immobilization system and a plexiglass slab (for the appropriate degrading of the beam's mean energy and widening of the fields) were fitted in a custom built chamber. Current half body irradiation techniques are used mainly for palliative purposes in metastatic diseases (prostate, lung and breast cancers) and involve photons as source of radiation [18][19][20][21][22][23][24][25][26]. In most of the cases, x-rays produced by linacs, γ rays produced by Cobalt Units [22] and even UVB rays, in phototherapy studies [24,] were utilized, yet only for highly palliative treatments in patients with a very short life expectancy (bony metastatic cancer [5,22,23], acute leukemia [25], metastatic carcinoma of the prostate [26]).…”
Section: Introductionmentioning
confidence: 99%